Comparison of Hemagglutination Inhibition Assay and Enzyme Immunoassay for Determination of Mumps and Rubella Immune Status in Health Care Personnel. Issue 5 (13th September 2013) - Kumakura, Shunichi; Shibata, Hiroshi; Isobe, Takeshi; Hirose, Masahiro; Ohe, Miki; Nishimura, Nobuhiro; Onoda, Keiichi; Nagai, Atsushi; Yamaguchi, Shuhei
<x xml:space="preserve">Abstract</x> Background Screening tests are available to determine immunity to vaccine‐preventable diseases, such as mumps and rubella. We aimed to define better assay for detecting immune status of health care personnel to vaccine‐preventable diseases. Methods Mumps and rubella antibodies of health care personnel at Shimane University Hospital were examined by hemagglutination inhibition assay (HI), comparing with those by enzyme immunoassay (EIA). Results A total of 910 sera from health care personnel were tested. There was poor correlation between HI and EIA in detecting mumps antibodies with correlation coefficient values (r) = 0.190 (P < 0.001), but in rubella antibodies HI and EIA were relatively well correlated (r = 0.930, P < 0.001). Seropositivity rate of HI versus EIA was found to be 65.7 versus 93.2, and 89.5 versus 86.5% for mumps and rubella, respectively. As compared with EIA, HI identified sixfold larger seronegative subjects in mumps. Moreover, in mumps, 88.8% of seronegative subjects detected by HI were seropositive by EIA, while 3.7% of seropositive subjects detected by HI were seronegative by EIA. In rubella, 2.1% of seronegative subjects detected by HI were seropositive by EIA, and 1.7% of seropositive by HI was seronegative by EIA. Conclusion Considerable difference between HI and EIA in determining immune status of health care personnel to mumps and rubella suggests beneficial use of EIA for the identification of accurate susceptible personnel who subsequently undergo an effective vaccination programs. Seroprevalence survey of health care personnel by using appropriate assay is essential for prevention and infection control strategies in health care settings.